Identification of deposit types of natural corundum by PIXE - Chulapakorn T. (Elsevier, 2014)
Natural corundum, one of the most important exports of Thailand, is a rare, durable and valuable gemstone. The value of these precious stones is determined by their visual appearances, including brilliance, color, fire (light dispersion) and luster. Corundum is an allochromatic mineral whose trace element concentration depends on the origin and has influence on price setting. This work attempts to use an alternative method to identify the geological deposits of rubies and sapphires found in the Thai market which came from various countries, e.g., Africa, Cambodia, Myanmar, Sri Lanka, Thailand and USA. Interrelations between most important major trace elements are the main results of this work. Quantitative analysis of trace elements were performed by particle-induced X-ray emission (PIXE) technique, using 2-MeV proton beam generated and accelerated by the 1.7 MV tandem accelerator at Chiang Mai University. The trace elements of interest are Ti, Cr, Fe and Ga. We have found that the relationships between the ratios of trace element concentration can be used to classify the deposit type. Moreover, this method shows a clear separation between two main types of geological deposits, basaltic and metamorphic deposits, which further helps in determining the gemstone origin. For example, the gemstones from Cambodia, Thailand and the USA can be classified as the basaltic deposits with their high concentration in Fe but low in Ti, while the gemstones from Africa, Myanmar and Sri Lanka are metamorphic deposits because they have low Fe but high Ti concentrations. Both deposits required plots of pairs of trace elements and their ratios in population field appearance in order to distinguish their origins. The advantageous of these methods appear to be a new and a sustainable procedure for determining gemstone origins. © 2014 Elsevier B.V. All rights reserved.